Colony-Level Viral Load Influences Collective Foraging in Honey Bees - Penn, Hannah J.; Simone-Finstrom, Michael D.; de Guzman, Lilia I.; Tokarz, Philip G.; Dickens, Rachel (Frontiers in Insect Science, 2022)
Nutrition is an important component of social insect colony health especially in the face of stressors such as parasitism and viral infections. Honey bees are known to preferentially select nectar and pollen based on macronutrient and phytochemical contents and in response to pathogen loads. However, given that honey bees live in colonies, collective foraging decisions may be impacted directly by forager infection status but also by colony health. This field experiment was conducted to determine if honey bee viral infections are correlated with pollen and nectar foraging and if these associations are impacted more by colony or forager infection. By comparing regressions with and without forager and colony variables and through structural equation models, we were able to determine the relative contributions of colony and forager virus loads on forager decisions. We found that foragers had higher numbers and levels of BQCV and CBPV but lower levels of DWV viruses than their respective colonies. Overall, individuals appeared to forage based a combination of their own and colony health but with greater weight given to colony metrics. Colony parasitism by Varroa mites, positively correlated with both forager and colony DWV-B levels, was negatively associated with nectar weight. Further, colony DWV-B levels were negatively associated with individually foraged pollen protein: lipid ratios but positively correlated with nectar weight and sugar content. This study shows that both colony and forager health can simultaneously mediate individual foraging decisions and that the importance of viral infections and parasite levels varies with foraging metrics. Overall, this work highlights the continued need to explore the interactions of disease, nutrition, and genetics in social interactions and structures.